Penurunan Nyeri Kaki Restless Leg Sindrome Pada Pasien Gagal Ginjal Kronik Melalui Intradialisis Range Of Motion Exercise Pasif - Putri Naila Fadlilatul Husna; Taufan Arif; Maria Diah Ciptaningtyas; Supono (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Introduction: Ureal buildup and inactivity can lead to complications of restless leg syndrome. The thing that is deeply felt in these complications is leg pain. The incidence of leg pain in RLS is 21.5â€“40%Â on a mild to moderate scale. RLS leg pain, if left continuously, can interfere with the patient's daily life and even affect the quality of life of patients with chronic kidney failure. The purpose of this study was to determine the effect of passive intradialysis range of motion exercise on the lower extremities on leg pain in patients with chronic renal failure.Method: The research design is